2016
DOI: 10.1016/j.virol.2016.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Interferon lambda and hepatitis C virus core protein polymorphisms associated with liver cancer

Abstract: the screening of these polymorphisms and functional studies would be useful in clinical practice for identifying groups at high risk of HCC development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Two studies were found to be eligible for inclusion in the process of hand search. Thus, 24 studies evaluating IL28B rs12979860 and rs8099917 were ultimately included in this meta-analysis, in which 18 studies evaluated the IL28B rs12979860 genotype CC vs CT/TT, [1,2,7,8,17–19,23,2533] and 15 studies evaluated the IL28B rs8099917 genotype TT vs TG/GG [1,7,9,17,19,23,26,30,32,3439] (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…Two studies were found to be eligible for inclusion in the process of hand search. Thus, 24 studies evaluating IL28B rs12979860 and rs8099917 were ultimately included in this meta-analysis, in which 18 studies evaluated the IL28B rs12979860 genotype CC vs CT/TT, [1,2,7,8,17–19,23,2533] and 15 studies evaluated the IL28B rs8099917 genotype TT vs TG/GG [1,7,9,17,19,23,26,30,32,3439] (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…[13] In HCC endemic areas (e.g., Taiwan), several risk factors have been identified, such as chronic infections of hepatitis C virus (HCV) [46] and/or hepatitis B virus (HBV), [79] as well as long-term exposure of fine particle pollution (particulate matter ≤ 2.5 μm [PM2.5]). [10] At initial presentation, most HCC patients were diagnosed with locoregionally advanced disease, which prevents from curative managements, [11] such as surgical resection, percutaneous ethanol injection, and radiofrequency ablation (RFA), [12] resulting in persistent high death rates.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we also evaluated SNPs in the IFNL3/4 region among Brazilians, an admixed population of three paternal lineages consisting of Native-American, European and African ancestries. Other studies with CHC patients treated with Peg-IFN-α/Ribavirin from different regions in Brazil focused on the SNPs rs12979860 and rs8099917, evidencing that CC and TT genotypes, respectively, presented favorable treatment outcomes ( Ge et al., 2009 ; Thomas et al., 2009 ; Cavalcante et al., 2012 ; Ramos et al., 2012 ; Moreira et al., 2016 ; Rizzo et al., 2016 ). Here, we confirmed the association of several SNPs with the responsiveness for treatment, highlighting the rs12979860 as the strongest predictor in obtaining SVR in patients treated with Peg-IFNα.…”
Section: Discussionmentioning
confidence: 99%